The Hindu world - Mittal,Sushil(Editor) Thursby,Gene(Editor) (The Routledge worlds, 2004)
"The Hindu World in the most authoritative and up-to-date single volume on Hinduism available today. In twenty-four chapters written by leading international scholars it provides a comprehensive and critical guide to the various literatures, traditions, and practices of Hinduism. Ideally tailored as an introduction to key topics in Hinduism and for use as a definitive reference source, the book offers fresh insights into many aspects of Hindu life."--BOOK JACKET.